MicroRNAs as Molecular Targets for Cancer Therapy: On the Modulation of MicroRNA Expression - Pedro M. Costa; Maria C. Pedroso de Lima (MDPI AG, 2013)
The discovery of small RNA molecules with the capacity to regulate messenger RNA (mRNA) stability and translation (and consequently protein synthesis) has revealed an additional level of post-transcriptional gene control. MicroRNAs (miRNAs), an evolutionarily conserved class of small noncoding RNAs that regulate gene expression post-transcriptionally by base pairing to complementary sequences in the 3' untranslated regions of target mRNAs, are part of this modulatory RNA network playing a pivotal role in cell fate. Functional studies indicate that miRNAs are involved in the regulation of almost every biological pathway, while changes in miRNA expression are associated with several human pathologies, including cancer. By targeting oncogenes and tumor suppressors, miRNAs have the ability to modulate key cellular processes that define the cell phenotype, making them highly promising therapeutic targets. Over the last few years, miRNA-based anti-cancer therapeutic approaches have been exploited, either alone or in combination with standard targeted therapies, aiming at enhancing tumor cell killing and, ideally, promoting tumor regression and disease remission. Here we provide an overview on the involvement of miRNAs in cancer pathology, emphasizing the mechanisms of miRNA regulation. Strategies for modulating miRNA expression are presented and illustrated with representative examples of their application in a therapeutic context.